Cadaveric Dissections to Determine Surface Landmarks Locating the Facial Artery for Filler Injections. (13th August 2020) - Tansatit, Tanvaa; Kenny, Elizabeth; Phumyoo, Thirawass; Jitaree, Benrita
Abstract: Background: The facial artery is a high-risk structure when performing filler injections at the nasolabial fold, buccal, and mandibular regions. Objectives: This study aimed to establish reference landmarks locating the course of the facial artery and its essential branches. Methods: Thirty-one embalmed cadavers were enrolled in this study. The course of the facial artery was observed in regard to the following reference points: masseter insertion, oral commissure, and common bony landmarks. The corner of the mouth was utilized as the landmark to measure the turning point of the facial artery. Results: Seven points were established to identify the course and turning point of the facial artery. These included the anterior masseteric, lateral mental, infraorbital, medial canthal, basal alar, post-modiolar (PMP), and supra-commissural (SCP) points. The course of the facial artery deviates at least twice at the lateral mental points and at the SCP or PMP. The facial artery appeared more medially when the artery turned at the PMP and SCP. It presented through the lateral channel if the turning point was solely at the PMP. Wherever the facial artery deviates, it can be divided into 3 segments: the mandibular, buccal, and nasolabial segments. The arterial course may deviate laterally from the mouth corner towards PMP. The nasolabial segment may also deviate laterally to the basal alar point at the alar grove for 0.5 to 1 cm. Conclusions: The deviation of facial artery closely relates with mandibular, buccal, and nasolabial segments. It is essential in avoiding arterial injury for physicians and surgeons who perform procedures in these areas.